Fire performance and regulatory considerations with modern methods of construction - Brian J. Meacham (Buildings & Cities, 2022)
Modern methods of construction (MMC) are becoming increasingly popular for a broad range of reasons. They are portrayed as providing significant economic and sustainability benefits over ‘traditional’ construction methods, 'e.g'. efficiencies gained by integrating the processes and technologies of design, manufacturing, and construction to result in higher quality buildings. It may also include a reduction in delivery times, more predictable costs, and fewer environmental impacts. However, MMC introduces increased complexity and can present challenges for traditional building regulatory approaches, especially those which focus on inspecting and verifying construction at many points in the construction process. With prefabricated components and modules this requires different approaches. Performance concerns arise for meeting the fire safety objectives of the final building. One particular fire challenge is the presence of void spaces, often needed to facilitate the connection of modules, which can potentially serve as avenues for the spread of fire, smoke, and hot gases. These fabrication issues, performance concerns, and regulatory challenges are explained. Fire performance issues are then explored for different regulatory typologies (prescriptive, performance based, market based), the verification of subsystem performance, and the compliance of installed components/whole building. Recommendations for regulatory frameworks are provided to provide increased confidence and reduced risks.   'Policy relevance' While every country needs to work within their regulatory framework and implement systems that work for them, it seems that with the growing use of MMC, additional regulatory guidance and oversight may be warranted to help increase confidence in the performance of modular buildings, in particular from a fire performance perspective. This might include the development of design and installation guidance, as well as regulatory review, inspection, and approval guidance. It may also mean the development of new test methods or standards, especially if materials or connection conditions ('e.g'. void spaces) warrant. As many countries have already mandated, it seems that the requirement for some form of quality assurance/quality control (QA/QC) procedures to help assure manufactured/fabricated components comply with regulatory requirements is an essential component.